Editorial: Open Access - Our Golden Route in Academic Publishing in an Increasingly Open World - Alison J Fields; Niki E Davis; Maggie Hartnett (Flexible Learning Association of New Zealand, 2015)
Open Access (OA) publishing, that is the immediate, online, free availability of research outputs without many of the restrictions imposed by traditional copyright agreements, is changing the landscape of scholarly publications. The Journal of Open, Flexible and Distance Learning is well positioned in the changing world of publishing with its focus on making high quality research in the Asia-Pacific region readily available to all. The recent inclusion of the Journal in the Directory of Open Access Journals highlights this commitment to accessibility. With that in mind, the three articles in this issue of the Journal explore the experiences of learners within three separate and distinct educational contexts in Aotearoa, New Zealand. Two of the articles are situated in the schooling sector where research on students learning at a distance is urgently needed to inform the development of more equitable practice worldwide. The third paper explores student engagement at the tertiary level, continuing the theme from the 2014 DEANZ conference relating to the 'e' in engagement. Using the article by Jeurissen as a focus, the editorial takes the time to highlight the role open, flexible and distance learning can play in the revitalisation of the New Zealand indigenous language, te reo Māori. The philosophy and methods of Open Access publishing are also discussed.